104 COST EFFECTIVENESS AND OUTCOME OF MANAGEMENT OF STROKES IN A NEWLY ESTABLISHED STROKE UNIT. Issue 1 (1st January 2007) - Jayawardena, S.; Ezike, U.; Venkatesan, J.; Volozhanina, E.; Clark, H.
Abstract : Background: Stroke is one of the leading causes that impose a considerable economic burden on the individual and society. The concept of an integrated stroke unit has been established in several countries around the world to improve the outcome of patients, as well as cut cost and reduce hospital stay. Objective: To see if a newly established stroke unit can improve the outcome of stroke patients as well as reduce the number of days spent in the hospital, thus reducing the overall cost to the patient and society. Method: Retrospective study done in a stroke unit in a community hospital for a period of 1 year, 2004-2005. When a patient came to the emergency room with symptoms suggestive of a stroke, the stroke team was activated and prompt action was taken to evaluate the patient by a neurologist followed by CT scan of the brain. The patients with strokes were transferred to the stroke unit for further management. Results: 298 patients were treated during this period. The average age was 71 years, with 141 (47.3%) female patients and 157 (52.6%) male patients. More than 92% of the strokes were ischemic in origin, and the majority of the time the underlying cause was poorly controlled hypertension and dyslipidemia. Overall, 14 (4.7%) patients died due to complications of the stroke. After activation of the stroke team, the average response time was 4.5 minutes and average length of stay was 11 days. Conclusion: Compared with other studies done on stroke patients managed in general wards, there was no difference in the length of stay or the outcome. But, obviously, the response time and workup were faster in an established stroke unit with an emergency response team. Larger prospective studies should be done to evaluate the cost effectiveness of managing patients in stroke units.